Effect of Plant Growth Regulators on Seed Germination and Seedling Growth of Stored Simaruba (Simaruba glauca Linn.) Seeds - Radhakrishnan, P.; Renganayaki, P. R. (Indian Forester, 2008)
A study was carried out on four month stored seeds of Simaruba glauca, to improve germination and vigour potential through growth regulators. The seeds were given eight treatments i.e. with two concentrations of IAA, IBA and GA3(200 and 400 ppm), seed coat removed and untreated control. The results of germination and vigour evaluation at 38 days after sowing revealed the beneficial effect of IAA 200ppm over the rest with 36.33% germination as against 11.67 per cent in control. Improvement of vigour by IAA 200ppm was four fold higher than the control. The root length and root biomass were increased significantly by GA3 treatment.